Improving the understanding of elementary school physical education teachers on the use of TGMD-2 - Djoko Nugroho; Baskoro Nugroho Putro; Hanik Liskustyawati; Sri Santoso Sabarini; Sunardi Sunardi; Budhi Satyawan (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Physical education, sports, and health teachers at elementary schools are obliged to teach their students about the correct basic movements. The basic movements that become the material for elementary school students are part of gross motor skills. The correct movement can be known well if the assessment is based on the process of the movement. The gross motor quality of students can be known by using the Test of Gross Motor Development-2 (TGMD-2). TGMD-2 is a gross motor skill test instrument for children from 3 to 9 years of age. This age range still represents elementary school students in grades 1 to 3. The assessment on the TGMD-2 is based on the correctness of the students' movements. Assessment based on the correct movement requires intensive mentorship so that teachers can understand the use of test instrument indicators. The mentorship lasted for 8 hours per day with practical material. The implementation of practice-based mentorship provides real experience for teachers in implementing TGMD-2. After undergoing mentorship activities, 88% of teachers have a percentage increase in test results above 90%. This increase shows the potential for successful use of TGMD-2 independently by the teacher and can improve the quality of the assessment of gross motor skills carried out by the teacher.